IFRS-16 and Firm Investment: Leasing Commitment and Intensity - Haris, Abdul; Nugroho, Arif Julianto Sri; Utami, Tri; Windar Amelia, Rizky (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2024)
Generally, this study examines the economic consequences of IFRS-16. Specifically, this study investigates whether commitment and leasing intensity affect firms' investment decisions. Previous literature focuses on constructive capitalization in operating leases and off-balance sheet financing as ex-ante impacts on financial statements. In contrast, this study examines the ex-post impact of leasing on financial statements. Furthermore, this study illustrates the aspects of lessee behavior in their decision to reduce operating leases before the effective date of IFRS-16 implementation. We used paired t-tests and regression with cluster robust standard error and samples from five countries with the largest leasing volume (United States, China, United Kingdom, Germany, and Japan). The observations start from 2011-2022. This study finds that operating lease intensity fell after issuing IFRS-16, while capital lease intensity arose. Operating and capital lease commitment affect firm investment positively, indicating that managers do not always use operating leases to reach opportunist reporting incentives.